Maternal Transmission of Human OGG1 Protects Mice Against Genetically- and Diet-Induced Obesity Through Increased Tissue Mitochondrial Content - Burchat, Natalie; Sharma, Priyanka; Ye, Hong; Komakula, Sai Santosh Babu; Dobrzyn, Agnieszka; Vartanian, Vladimir; Lloyd, R. Stephen; Sampath, Harini (Frontiers in Cell and Developmental Biology, 2021)
Obesity and related metabolic disorders are pressing public health concerns, raising the risk for a multitude of chronic diseases. Obesity is multi-factorial disease, with both diet and lifestyle, as well as genetic and developmental factors leading to alterations in energy balance. In this regard, a novel role for DNA repair glycosylases in modulating risk for obesity has been previously established. Global deletion of either of two different glycosylases with varying substrate specificities, Nei-like endonuclease 1 (NEIL1) or 8-oxoguanine DNA glycosylase-1 (OGG1), both predispose mice to diet-induced obesity. Conversely, enhanced expression of the human OGG1 gene renders mice resistant to obesity and adiposity. This resistance to diet-induced obesity is mediated through increases in whole body energy expenditure and increased respiration in adipose tissue. Here, we report that hOGG1 expression also confers resistance to genetically-induced obesity. While Agouti obese (Ay/a) mice are hyperphagic and consequently develop obesity on a chow diet, hOGG1 expression in Ay/a mice (Ay/aTg) prevents increased body weight, without reducing food intake. Instead, obesity resistance in Ay/aTg mice is accompanied by increased whole body energy expenditure and tissue mitochondrial content. We also report for the first time that OGG1-mediated obesity resistance in both the Ay/a model and diet-induced obesity model requires maternal transmission of the hOGG1 transgene. Maternal, but not paternal, transmission of the hOGG1 transgene is associated with obesity resistance and increased mitochondrial content in adipose tissue. These data demonstrate a critical role for OGG1 in modulating energy balance through changes in adipose tissue function. They also demonstrate the importance of OGG1 in modulating developmental programming of mitochondrial content and quality, thereby determining metabolic outcomes in offspring.